Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0300060518767031
|View full text |Cite|
|
Sign up to set email alerts
|

Salivary gland ultrasound is linked to the autoimmunity profile in patients with primary Sjögren’s syndrome

Abstract: Objective Salivary gland ultrasound (SGU) is a reliable technique for assessing the salivary glands in patients with primary Sjögren's syndrome (pSS). The aim of this study was to elucidate the relationship between SGU findings and autoimmunity in patients with pSS. Methods Patients with pSS underwent an SGU assessment. The patients were classified into three groups according to their autoimmunity profile: the complete positive group (positive rheumatoid factor, antinuclear antibodies, and anti-Ro/anti-La anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The latest was proposed in 2019 by the OMERACT task force and is also focused on parenchymal inhomogeneity (11). Of note, two different SGUS scoring systems provided identical results in this study, and this might be relevant to facilitate, at least in part, the evaluation and the comparison of the previous studies which used different scoring systems (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), although in our study, a bias in classifying the same US image simultaneously at patient bedside using two different, but quite similar, scoring systems could be present.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The latest was proposed in 2019 by the OMERACT task force and is also focused on parenchymal inhomogeneity (11). Of note, two different SGUS scoring systems provided identical results in this study, and this might be relevant to facilitate, at least in part, the evaluation and the comparison of the previous studies which used different scoring systems (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), although in our study, a bias in classifying the same US image simultaneously at patient bedside using two different, but quite similar, scoring systems could be present.…”
Section: Discussionmentioning
confidence: 53%
“…Although with some limitations for the reasons mentioned above, several studies reported associations between sonographic parenchymal inhomogeneity and clinical, laboratory, and pathological pSSrelated features, such as reduced salivary flow rate, presence of anti-Ro/SSA and/or anti-La/SSB antibody, positive lip biopsy, etc. (18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we demonstrated that patients with abnormal SGUS scores did not differ significantly from those with normal findings with regard to age at examination, age at diagnosis, or disease duration in accordance with previous studies. 15,35,39 Mossel et al 35 found that there is no difference in disease duration between patients with medium positive or high-positive SGUS scores. It could be postulated that after certain disease duration there is stabilization in the SGUS lesions, as happened with the production of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Several studies demonstrated good correlation of SGUS with other imaging modalities for diagnosing SS, 14 autoantibodies and dry mouth and eye symptoms, and minor pathological changes in the salivary gland. [15][16][17] While many studies have focused on primary SS, limited studies examined the role of SGUS in patients with secondary SS. 18 The aims of this study were to 1) evaluate the performance of SGUS for the diagnosis of sSS in patients with SLE, and 2) identify the relationship between SGUS findings with clinical and laboratory findings in patients with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…These associations could help to select a more severe subset of patients with pSS. 35,36 On the other hand, age-related artifacts can be a confusing factor. Future studies will help to clarify the diagnostic, classification or prognostic rule of SGU in the management of patients with EOpSS.…”
Section: Bronchi and Lungmentioning
confidence: 99%